YAP Deficiency Attenuates Pulmonary Injury Following Mechanical Ventilation Through the Regulation of M1/M2 Macrophage Polarization - Luo Q; Luo J; Wang Y (Dove Medical Press, 2020)
Qiong Luo, Jing Luo, Yanlin Wang Department of Anesthesiology, Zhongnan Hospital of Wuhan University, Wuhan, Hubei 430071, People’s Republic of ChinaCorrespondence: Yanlin WangDepartment of Anesthesiology, Zhongnan Hospital of Wuhan University, Wuhan, Hubei 430071, People’s Republic of ChinaEmail ylwang917@163.comBackground: Evidences indicate that the balance between macrophage M1 and M2 polarization is essential for the regulation of pulmonary inflammation during mechanical ventilation (MV). Yes-associated protein (YAP) is a key component of the Hippo pathway and was suggested to regulate macrophage polarization. This study was designed to investigate whether YAP contributes to pulmonary inflammation during MV.Methods: Wild-type and macrophage YAP knockout mice were mechanically ventilated for 12 hours to induce pulmonary injuries. At the end of MV, animals were sacrificed for pulmonary tissue collection and macrophage isolation. In addition, the induction of macrophage polarization was performed in isolated macrophages with or without YAP overexpression in vitro. Pulmonary injuries, YAP expression, macrophage polarization and cytokines were measured.Results: Here, we show that MV induces lung injury together with pulmonary inflammation as well as upregulated YAP expressions in pulmonary macrophages. In addition, our results indicate that YAP deficiency in macrophages attenuates pulmonary injury, accompanied with decreased production of pro-inflammatory cytokines including IL (interleukin)-1β, IL-6 and tumor necrosis factor-alpha (TNF-α). Moreover, both in vivo and in vitro studies indicate that YAP deficiency enhances M2 polarization while inhibits M1 polarization. In contrast, YAP overexpression inhibits the induction of M2 polarization but improves M1 polarization.Conclusion: Our results report for the first time that the induction of YAP in macrophages contributes to pulmonary inflammation during MV through the regulation of M1/M2 polarization.Keywords: yes-associated protein, macrophage polarization, pulmonary inflammation, mechanical ventilation